NOTES ON MACROCHELES (ACARI: MACROCHELIDAE) ASSOCIATED WITH SCARABAEID DUNG BEETLE IN RAJA AMPAT, WAIGEO ISLAND, WEST PAPUA, INDONESIA - Hartini , Sri (Treubia, 2014)
Four species of the genus Macrocheles belonging to the family Macrochelidaewere reported from Raja Ampat, Waigeo Island, West Papua, including M. timikaensisHartini & Takaku 2006 and M. dispar (Berlese 1910) as new record to the Island. Twonew species and the deutonymph of M. timikaensis Hartini & Takaku 2006 are described.